Integration Of Multicultural Values Through Religious Holidays And Cultural Activities In Ngabang Elementry Schools - Sulistyowati, Dewi; Faizal Amin (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study examines the implementation of multicultural education in a Public Elementary School in Ngabang District which has cultural, religious, and ethnic diversity. The results of the study indicate that the school has succeeded in integrating multicultural values through the Celebration of Religious Holidays and Cultural Activities . These activities not only foster a sense of pride in the cultural identity of each student, but also build an attitude of mutual respect, tolerance, and inclusivity. Students' positive attitudes towards diversity are reflected in harmonious social interactions and enthusiasm for participating in cultural and religious activities. The multicultural education approach applied, supported by the theories of experts such as Ki Hajar Dewantara, James A. Banks, and Tilaar, emphasizes the importance of inclusive education and real-life experience-based education to shape the character of tolerant and open students. These findings indicate that multicultural education can be an effective tool in creating a peaceful learning environment and building a harmonious and socially just Indonesian society.